The Non-Declinable Nouns in Surat al-Fath According to Abu Ishaq al-Zajjaj: A Morphological Analysis - Farhan Mubarok Lubis (Pusdikra-Publishing.com, 2025)
This study examines non declinable nouns in Surat al Fath through a morphological analysis based on Abu Ishaq al Zajjaj work Ma Yansarif wa Ma La Yansarif. The research focuses on identifying non declinable nouns in the surah and explaining their morphological characteristics particularly their resistance to inflection across grammatical contexts. Using a descriptive analytical method and library research this study analyzes the relevant verses and classifies the types of non declinable nouns found in Surat al Fath. The findings show that non declinable nouns do not accept tanwin and are not marked with kasrah unless preceded by the definite article al. Without al they take dammah in the nominative and fathah in both the accusative and genitive cases. A total of 137 non declinable forms appear across 29 verses of Surat al Fath including nouns adverbs and proper names.